2011
DOI: 10.5860/crl-166
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacy Instruction and Assessment in an Honors College Science Fundamentals Course

Abstract: The Washington State University Honors College course, UH 290, "Science as a Way of Knowing," engages freshmen in scientific inquiry and scholarly literature research. The UH 290 instructor, a learning design consultant, and two librarians collaborated to develop and deliver the course's information literacy curriculum. The team used student surveys, research blogs, case studies, library instruction sessions, homework problem sets and exams. Students gained from scaffolded instruction including hands-on practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…The findings of Johnson, Anelli, Galbraith, and Green (2011) agree with those of the present study: their Honors students demonstrated the same problems as the others in locating the library's resources.…”
Section: Do Different Student Populations (Class Years Honors Studensupporting
confidence: 91%
“…The findings of Johnson, Anelli, Galbraith, and Green (2011) agree with those of the present study: their Honors students demonstrated the same problems as the others in locating the library's resources.…”
Section: Do Different Student Populations (Class Years Honors Studensupporting
confidence: 91%
“…There were also discussions about the characteristics of historian-produced sources, and what makes scholarly, primary, or secondary sources. This finding substantiates the work from Johnson (2011), which showed students incorporate more scholarly works into their writing after library instruction. Regarding the Argument Building outcome, the library sessions helped guide students to relevant historical and scholarly materials.…”
Section: Discussionsupporting
confidence: 74%
“…23 Johnson did a recent study with a WSU Honors College course concluding that after library instruction, students incorporate more scholarly works in their writing. 24 The Roots LRAs also include pointed library instruction that is most likely connected to student success with utilizing scholarly works in their essays.…”
Section: Discussionmentioning
confidence: 99%